KINERJA KEPALA DESA MEYERGA DISTRIK MOKSONA BARAT KABUPATEN TELUK BINTUNI - OROCOMNA, YULIANUS; PANGKEY, MASJE SILIJA; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: This research was conducted to describe the performance of Meyerga village chief from West Moksona District,Teluk Bintuni Regency. The results of this study are expected to provide benefits for the development of publicadministration science, especially about performance, and practically become an evaluation for Meyerga village chief fromWest Moksona District, Teluk Bintuni Regency to improve his/her performance. This research uses qualitative designfocusing on work quality, quantity and timeliness. Data were collected through interviews with informants from the WestMoksona District government elements, the government and villagers of Meyerga village, followed by our own observationand documentation studies. Data analysis were done through data reduction, data display, data conclussionsdrawing/verification. The result shows that the performance of the village chief in the development program is going wellbecause the development implemented until now has been running as planned. The performance in running the governmenthas not been good because of the lack of knowledge and skills possessed by the village chief and other village officials inunderstanding the rules and work procedures of governance, the mastery of village government administration included.The performance of the village chief in the implementation of community development is already good due to his presenceas a respected community leader and also the support of community leaders and religious leaders for the village chief inconducting community development. The performance of the village chief in the community empowerment program hasnot been good due to lack of clarity of village government programs to improve the community's capacity in terms ofeducation, community development and to young generation and women. This research concludes that the performancesof Meyerga village chief of West Moksona District of Teluk Bintuni Regency, West Papua Province based on work quality,work quantity and utilization of working time has been well done in the field of development and community developmentand has not run well in the field of government, and community empowerment. It is therefore advisable to undertaketraining for making village government work plans, complementing work facilities, continuously strengtheningrelationships with religious leaders and community leaders. Adapting the work programs in the field of communityempowerment focused on youth empowerment, community development and women is needed.Keywords: Performance, Village Chief